The Compressive Bars with Bounded Displacement as the Task of Optimal Control - Mikulski, L. (Engineering Transactions, 1993)
The beam with bounded displacement compressed by the axial force is considered as an optimal control task. The constraints relative to displacement of the bar axis could be active pointwise or in same domain. To salve the task, maximum principle shall be used; necessary conditions reduce the problem of optimal control to a multipoint boundary value problem for ordinary differential equations. The boundary value problems with jump conditions are solved by multiple-shooting techniques.